Cytotoxicity Test on Breast Cancer Cell Lines T-47D treated with Pisang Kepok Peel Extract (Musa balbisiana) - Wardati, Fauchil; Holil, Kholifah; Syarifah, Umaiyatus (Future Science, 2018)
Introduction: Utilization of natural ingredients such fruit as a breast cancer treatment agent is beginning to be widely studied by scientists. The goal is to reduce the side effects of chemotherapy agents. One of the potential natural ingredients as anticancer is Pisang Kepok peel (Musa balbisiana). This kind of banana contains various phytochemical compounds and high antioxidant activity that can induce cancer cell apoptosis. The purpose of this research is to know the IC50 value of Pisang Kepok peel extract thus can be known its potential as an anticancer agent. The lower of IC50 value is more cytotoxic. Method: This research is experimentally done by using CRD (Completely Randomized Design). The stages of this research are extraction and cytotoxic test (MTT assay). The extraction method was used maceration (ethanol 95%). The cytotoxic test was performed by giving Pisang Kepok unripe peel extract on the T-47D cell lines, then read the absorbance with ELISA reader at ? 595 nm and analyzed by SPSS Probit. Conclusions: Based on this results, it can be concluded that Pisang Kepok peel extract has moderate cytotoxic to T-47D cell lines, therefore indicate its potential as a candidate for breast cancer chemoprevention agents, especially at high concentrations (>250 ?g/mL).